PRESSURE WAVE PROPAGATION IN SNOW WITH NONUNIFORM PERMEABILITY. - Yen,Yin-Chao; fan,S. S. T. (1966)
A mathematical analysis of pressure wave propagation through a deep layer of snow with nonuniform permeability is presented. The study extends previous investigations on porous media in which the physical properties and imposed boundary conditions have been assumed or kept constant. Two cases of boundary conditions were considered. Case I: imposed pressure at the boundary remains constant. Case II: imposed pressure at the boundary falls exponentially with time. Darcy's law was assumed to be valid. The nonlinear differential equation was solved by the finite difference technique and the results are presented in terms of dimensionless variables. (Author)